2011
DOI: 10.1186/1749-8546-6-8
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extract (EGb761) inhibits mitochondria-dependent caspase pathway and prevents apoptosis in hypoxia-reoxygenated cardiomyocytes

Abstract: BackgroundEGb761 is a standard extract from the leaves of Ginkgo biloba (Yinxing) containing ginkgo-flavone glycosides and terpenoid. The flavonoid components of EGb761 scavenge free radicals and protect myocardia from ischemia-reperfusion injury. The present study aims to determine the effects of the active compounds of EGb761 on mitochondria-dependent caspase pathway.MethodsCardiomyocytes were exposed to 24 hours of hypoxia and four hours of reoxygenation, and pretreated with EGb761, bilobalide and quertceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
(21 reference statements)
0
20
0
Order By: Relevance
“…by activating the nuclear factor erythroid-derived 2-related factor 2 (Nrf2) transcription factor pathway. 120,121 Resveratrol as well as quercetin, catechins, and procyanidins have been demonstrated to counteract oxidative stress-induced apoptosis by increasing the level of mitochondrial antioxidant enzymes and modulating specific signalling pathways and kinase activities, [122][123][124][125][126][127][128][129][130][131] which result in a complex regulation of the balance between pro-and anti-apoptotic Bcl-2 family members. [132][133][134][135][136] These activities might be due to the capability of polyphenols to accumulate in mitochondria.…”
Section: Polyphenols As Cytoprotective Compounds Via Their Antioxidanmentioning
confidence: 99%
“…by activating the nuclear factor erythroid-derived 2-related factor 2 (Nrf2) transcription factor pathway. 120,121 Resveratrol as well as quercetin, catechins, and procyanidins have been demonstrated to counteract oxidative stress-induced apoptosis by increasing the level of mitochondrial antioxidant enzymes and modulating specific signalling pathways and kinase activities, [122][123][124][125][126][127][128][129][130][131] which result in a complex regulation of the balance between pro-and anti-apoptotic Bcl-2 family members. [132][133][134][135][136] These activities might be due to the capability of polyphenols to accumulate in mitochondria.…”
Section: Polyphenols As Cytoprotective Compounds Via Their Antioxidanmentioning
confidence: 99%
“…A standardized Ginkgo biloba extract 761 (EGb 761) has been used as strong antioxidative and neuroprotective agent to treat neurodegenerative diseases [21]. Furthermore, several researches have indicated that EGb 761 protects against renal, myocardial, and cerebral ischemiareperfusion injury [22][23][24][25], and improves hepatic DNA damage and liver microcirculation after warm ischemia [26,27]. Ginkgo biloba Dropping Pill (GBDP) is a unique Ginkgo biloba leaf extract preparation produced in China for treating angina pectoris and cerebral infarction caused by blood stasis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous report suggested that the extract from the whole plant of C. orientalis promoted antidengue virus effect using MTT assay [ 2 ]. The leaf extract also promoted effective inhibition of human hepatocarcinoma (HepG2) [ 3 ]. It was previously reported that terpenoid compounds including ent-halimane diterpenes; chettaphanin I and chettaphanin II, sesquiterpenes; 8-hydroxy-alpha-guaiene, spathulenol, cyperenoic acid, and triterpenes; and taraxerol and acetoxyaleuritolate were the major components in C. orientalis [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some unusual aromatic diglycosides including 4′′-O-galloyl-violutoside and 4′′-O-galloyl-benzyl-O- α -L-rhamnopyranosyl-(1→6)- β -D-glucopyranoside and some flavonoids such as isovitexin and apigenin glycosides were found in the aerial part of this plant [ 7 ]. Moreover, the leaves were also reported to contain some phenolics and flavonoids including chlorogenic acid, epicatechin, and quercetin [ 3 ]. Despite reports suggesting some biological activities of C. orientalis extract, the ethnomedical use of this plant as tonic and agent to treat flatulence and stomachache is yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%